2023
DOI: 10.1007/s10071-023-01753-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel object recognition in Octopus maya

Abstract: The Novel Object Recognition task (NOR) is widely used to study vertebrates' memory. It has been proposed as an adequate model for studying memory in different taxonomic groups, allowing similar and comparable results. Although in cephalopods, several research reports could indicate that they recognize objects in their environment, it has not been tested as an experimental paradigm that allows studying different memory phases. This study shows that two-month-old and older Octopus maya subjects can differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Not only the presence of a sandy bottom but also the presence of objects, such as seashells, stones, and plastic toys, in the ENR tank played a positive role as cephalopods possess high cognitive abilities and need a continuous motor and cognitive stimulation [17,83]. This ability to interact with objects has been found in Octopus maya under laboratory conditions [43] and also in Octopus vulgaris in the wild [51]. Cuttlefish farmed in environments with objects, such as artificial algae and rocks, showed normal development of learning and memory, unlike those in unenriched environments [36].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Not only the presence of a sandy bottom but also the presence of objects, such as seashells, stones, and plastic toys, in the ENR tank played a positive role as cephalopods possess high cognitive abilities and need a continuous motor and cognitive stimulation [17,83]. This ability to interact with objects has been found in Octopus maya under laboratory conditions [43] and also in Octopus vulgaris in the wild [51]. Cuttlefish farmed in environments with objects, such as artificial algae and rocks, showed normal development of learning and memory, unlike those in unenriched environments [36].…”
Section: Discussionmentioning
confidence: 91%
“…Although many studies have shown the influence of EE on terrestrial vertebrates, for example, rats [24,25], chimpanzees [26], and black bears [27], and on fish, such as African catfish [28], black rockfish [29], zebrafish [30,31], chinook salmon [32], rainbow trout [33], and seabream [34] that are used in research and aquaculture, there are only a few studies that have evaluated the effects of different types of environmental enrichment on cephalopod mollusks. Among these studies, the species mainly investigated include Sepia officinalis [35,36], Sepia pharaonis [37,38], Octopus bimaculoides [39,40], Callistoctopus aspilosomatis [41], Enteropus octdofleini [42], and Octopus maya [43]; however, similar studies on the behavior of O. vulgaris are lacking. The focus of papers on this species has been more on individual learning [44,45], social behavior [46,47], feeding behavior [48,49], problem solving [50], and play and puzzle solving [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Using its suckers, the octopus moves along the walls of the tank in an ascending, descending, and horizontal way, extending all arms to move. This behavior usually occurs when the octopus is presented with new objects or stimuli; possibly allowing a better visual exploration (see Vergara-Ovalle et al 2023) (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…4B; S1E). This behavior can occur during feeding, but also in other contexts such as exploration (Vergara-Ovalle et al, 2023; Gutfreund et al, 1998), social interaction (Scheel et al, 2016) or den maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…The success of the crab trap in capturing O. tetricus may be due to the methods employed by octopuses to explore novel objects. Octopuses typically use visual and tactile exploration to investigate novel objects, but only tactile assessment of known objects (Ovalle et al 2023). Of the three trap types, the ne mesh of the crab traps allowed for the greatest visual exploration of the arti cial lure from all angles and any distance.…”
Section: Octopus Capturementioning
confidence: 99%